Wound Healing Potential of Sargassum plagiophyllum Extract on Mice Model with Incision Lesion - Mandasari, Andita Ayu; A'isyi, Nadia Rahadatul; Herawati, Dheasy (Jurnal Biologi Tropis, 2025)
The skin serves as the body's outer protection against infection and plays an important role in water and electrolyte balance. The skin is often injured which increases the risk of infection if the wound does not close immediately. This study explored the potential of concentrated extract of Sargassum plagyophyllum in healing incision wounds in mice. Mice were given a 1 cm incision wound and then given CaCl2 S. plagyophyllum extract as the treatment group, povidine iodine as the positive control group, while the negative control group was not given anything. Macroscopic results showed that the wounds in the treatment group healed on day 17, while the negative and positive groups healed on days 15 and 16. Microscopic images showed that the inflammatory phase of wound healing was seen on day five in all groups which showed a normal phase of wound healing. These results indicate that the CaCl2 extract of S. plagyophyllum has the same potency as the positive group, but it is very important to consider the right formulation so that the effectiveness can be increased and faster in wound healing in future studies.